Faktor-Faktor yang Memengaruhi Kemiskinan Rumah Tangga Bekerja di Pulau Jawa - Yohana Madame Hutahaean; Jeffry Raja Hamonangan Sitorus (Seminar Nasional Official Statistics, 2022)
Poverty causes people cannot meet prosperity in their lives, so it must be eradicated according to the first goals of the SDGs. Java Island becomes the region with the highest percentage of poor people in Indonesia in 2021 even though the participation of poor household in work is high. The study aims to know the general description of the characteristics of working household poverty, to know the factors that significantly influence the working household poverty and to know the tendency of each predictor variables that significantly influence the working household poverty in Java Island in 2021. The method used is binary logistic regression. The results showed that factors that significantly influenced the working household poverty are number of household members, marital status of household head, gender of household head, the education level of household head, the occupation sector of household head, the working status of the head of the household, the number of household work hours a week, and the number of work household. The conclusion is that to alleviate the working hoousehold poverty, the government is expected to encourage family planning programs, socialize readiness before marriage, ensure that there is no discrimination against women in work, pay attention to the quality of education, and help to provide the better agricultural equipment.